2004
DOI: 10.1021/es035263i
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of the Herbicide Dichlobenil and the Metabolite 2,6-Dichlorobenzamide on Soils and Aquifer Sediments

Abstract: The worldwide used herbicide dichlobenil (2,6-dichlorobenzonitrile) has resulted in widespread presence of its metabolite 2,6-dichlorobenzamide (BAM) in pore- and groundwater. To evaluate the transport of these compounds we studied the sorption of dichlobenil and BAM in 22 sediment samples of clayey till, sand, and limestone including sediments exhibiting varying oxidation states. Dichlobenil sorbed to all investigated sediments, with a high sorption in topsoils (Kd = 7.4-17.4 L kg(-1)) and clayey till sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…The former possibility is at least partly true as the compounds in question were found to adsorb onto the soil (Dagnac et al, 2005) and significant sorption capacity of some vadose zone solids could be demonstrated (Clausen et al, 2004). On the other hand, the transit time of the compounds through the several meters thick vadose zone may exceed the time elapsed since the application of AT was halted.…”
Section: Discussionmentioning
confidence: 99%
“…The former possibility is at least partly true as the compounds in question were found to adsorb onto the soil (Dagnac et al, 2005) and significant sorption capacity of some vadose zone solids could be demonstrated (Clausen et al, 2004). On the other hand, the transit time of the compounds through the several meters thick vadose zone may exceed the time elapsed since the application of AT was halted.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the linear Freundlich isotherm produced similar results at depths greater than 0.9 m, the Langmuir isotherm was not used at these depths in order to save computing time. Clausen et al (2004) found a linear correlation between the total organic carbon content (TOC) and sorption of dichlobenil and BAM as long as the TOC > 1.0 g kg −1 :…”
Section: Vadose Zone Modelmentioning
confidence: 98%
“…Clausen et al, 2004;Sprankle et al, 1975;Tuxen et al, 2000), controlled fieldscale experiments exploring the rate and pathways of transport (e.g. Boesten and van der Pas, 2000;Funari et al, 1998) and regional and national monitoring programmes comparing the degree and character of contamination between different types of catchments (e.g.…”
Section: Introductionmentioning
confidence: 99%